Knowledge about warfarin treatment in patients with atrial fibrillation or mechanical prosthetic valves - Vásquez Ortiz, Lady Rojana (2022)
Objective. To determine the degree of knowledge about warfarin treatment in patients with atrial fibrillation or with mechanical prosthetic valves. Materials and methods. Descriptive, observational, cross-sectional study. The OAK test was applied to all adult patients with a diagnosis of atrial fibrillation or with mechanical prosthetic valves treated with warfarin, who attended the hematology consultation from May 17 to November 10, 2022, at the “Instituto Nacional Cardiovascular Carlos Alberto Peschiera Carrillo”. Results. A total of 150 patients participated, 64% were male, with a mean age of 60.3 ± 15 years, 45.3% with a diagnosis of atrial fibrillation and 54.7% with mechanical prosthetic valves. The mean OAK test score was 44.4% (8.4/19), only 6% (n=9) achieved a satisfactory score ≥75.0%, the percentage of correct answers according to dimensions was: 68 % in forms of use, 39.3% in interactions and complications and 41.1% in INR control. A 40.7% did not understand the meaning of the term INR and 81.3% did not know their optimal values. Conclusions. The patient’s degree of knowledge about warfarin treatment was inadequate; both in its use, interactions and complications. Considering that it is a difficult drug to use, due to its narrow therapeutic window and its multiple interactions, inadequate knowledge of its use may contribute to inappropriate anticoagulation.